2022
DOI: 10.1002/er.7880
|View full text |Cite
|
Sign up to set email alerts
|

Strategy improvements to minimize the drawbacks of geothermal investments by using spherical fuzzy modelling

Abstract: This study aims to evaluate the significant risks in geothermal energy investments. For this purpose, a model is suggested by considering the Spherical fuzzy DEMATEL technique. With the help of the literature examination, eight important risks are identified for these projects. In the following step, their weights are calculated so that more significant risk issues can be understood.Another calculation is also performed by triangular fuzzy DEMATEL to check the consistency of the analysis results. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 62 publications
(71 reference statements)
0
4
0
2
Order By: Relevance
“…According to Lebbihiat et al [34], despite these issues, there are some disadvantages in the process of obtaining electricity with geothermal energy. Yüksel et al [35] identified that in this process, if the source water obtained from the underground is not returned to this source, a water problem occurs in the region. This situation causes agricultural production in the region to be adversely affected.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lebbihiat et al [34], despite these issues, there are some disadvantages in the process of obtaining electricity with geothermal energy. Yüksel et al [35] identified that in this process, if the source water obtained from the underground is not returned to this source, a water problem occurs in the region. This situation causes agricultural production in the region to be adversely affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, ranking results of the emerging economies are indicated in Table 4. The distances to the best (𝐷 𝑖 + ) and worst alternatives (𝐷 𝑖 − ) for each criterion are computed by using Equations ( 34) and (35). Similarly, the relative closeness to the ideal solutions (𝑅𝐶 𝑖 ) is computed with Equation (36).…”
Section: B Ranking the Electricity Production Capacities Of Emerging ...mentioning
confidence: 99%
“…In traditional DEMATEL [48], experts' hesitation is ignored. This is the first time that the spherical fuzzy version of DEMATEL [49,50] has been described in the literature for tackling this issue [51]. As a demonstration of the method's applicability, a case study is provided in the following section.…”
Section: Spherical Fuzzy Dematelmentioning
confidence: 99%
“…Son kategori ise yeşil hastanelerde verimlilik artışı olmasıdır. Böylelikle personelin hasta olması veya devamsızlık yapması önlenerek hastanede sunulan hizmet kalitesi artar ve süreklilik sağlanır [18].…”
Section: Yeşil Hastane Kavramıunclassified